Scalable video streaming over OpenFlow networks: An optimization framework for QoS routing - Egilmez, H. E.; Gorkemli, B.; Tekalp, A. M.; Civanlar, S. (2011 18th IEEE International Conference on Image Processing, 2011)
OpenFlow is a clean-slate Future Internet architecture that decouples control and forwarding layers of routing, which has recently started being deployed throughout the world for research purposes. This paper presents an optimization framework for the OpenFlow controller in order to provide QoS support for scalable video streaming over an OpenFlow network. We pose and solve two optimization problems, where we route the base layer of SVC encoded video as a lossless-QoS flow, while the enhancement layers can be routed either as a lossy-QoS flow or as a best effort flow, respectively. The proposed approach differs from current QoS architectures since we provide dynamic rerouting capability possibly using non-shortest paths for lossless and lossy QoS flows. We show that dynamic rerouting of QoS flows achieves significant improvement on the video's overall PSNR under network congestion.